2008
DOI: 10.1016/j.jcta.2008.01.002
|View full text |Cite
|
Sign up to set email alerts
|

A lower bound for the length of a partial transversal in a Latin square

Abstract: It is proved that every n × n Latin square has a partial transversal of length at least n − O(log 2 n). The previous papers proving these results (including one by the second author) not only contained an error, but were sloppily written and quite difficult to understand. We have corrected the error and improved the clarity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
69
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(74 citation statements)
references
References 4 publications
5
69
0
Order By: Relevance
“…Indeed, any linear upper bound on (n) would imply the existence of a constant c such that every Latin square of order n has a partial transversal of length nc. The best result to date is that every Latin square has a partial transversal of length nO(prefixlog2n).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, any linear upper bound on (n) would imply the existence of a constant c such that every Latin square of order n has a partial transversal of length nc. The best result to date is that every Latin square has a partial transversal of length nO(prefixlog2n).…”
Section: Introductionmentioning
confidence: 99%
“…Now our desired matching corresponds to a transversal. Hatami and Shor [9] proved that if K m,m is a union of m 1-factors F 1 , F 2 , . .…”
Section: Introduction and Notationmentioning
confidence: 99%
“…The best known lower bound is due to Hatami and Shor , who showed that every Latin square of order n has a partial transversal of size nOfalse(normallog2false(nfalse)false).…”
Section: Introductionmentioning
confidence: 99%